2014
DOI: 10.1073/pnas.1416955111
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of breast pathologies using nonlinear microscopy

Abstract: Rapid intraoperative assessment of breast excision specimens is clinically important because up to 40% of patients undergoing breast-conserving cancer surgery require reexcision for positive or close margins. We demonstrate nonlinear microscopy (NLM) for the assessment of benign and malignant breast pathologies in fresh surgical specimens. A total of 179 specimens from 50 patients was imaged with NLM using rapid extrinsic nuclear staining with acridine orange and intrinsic second harmonic contrast generation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
161
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(167 citation statements)
references
References 45 publications
3
161
0
Order By: Relevance
“…Because physical sectioning accounts for the vast majority of processing delay for both FFPE and FSA histology, optical sectioning can dramatically reduce processing times and enable intraoperative histological examination in scenarios where FFPE and FSA histology are too time consuming. Various methods have been proposed for imaging breast, prostate and other surgical margins without physical sectioning, including optical coherence tomography (OCT) [18][19][20][21][22], reflectance confocal microscopy (RCM) [23,24], confocal fluorescence microscopy (CFM) [25][26][27][28][29], structured illumination microscopy (SIM) [30], light sheet microscopy [31], microscopy with ultraviolet surface excitation (MUSE) [32,33], and nonlinear microscopy (NLM) [34][35][36][37][38]. Stimulated Raman scattering (SRS) has also been demonstrated for surgical histology [39], but typically has appreciably lower imaging speed or signal to noise ratio when performed without physical sectioning in reflectance mode.…”
Section: Introductionmentioning
confidence: 99%
“…Because physical sectioning accounts for the vast majority of processing delay for both FFPE and FSA histology, optical sectioning can dramatically reduce processing times and enable intraoperative histological examination in scenarios where FFPE and FSA histology are too time consuming. Various methods have been proposed for imaging breast, prostate and other surgical margins without physical sectioning, including optical coherence tomography (OCT) [18][19][20][21][22], reflectance confocal microscopy (RCM) [23,24], confocal fluorescence microscopy (CFM) [25][26][27][28][29], structured illumination microscopy (SIM) [30], light sheet microscopy [31], microscopy with ultraviolet surface excitation (MUSE) [32,33], and nonlinear microscopy (NLM) [34][35][36][37][38]. Stimulated Raman scattering (SRS) has also been demonstrated for surgical histology [39], but typically has appreciably lower imaging speed or signal to noise ratio when performed without physical sectioning in reflectance mode.…”
Section: Introductionmentioning
confidence: 99%
“…A water immersion objective was selected for 20× imaging in order to be consistent with our previous study. 24 Each image frame was acquired at 1024 × 1024 pixels. With the 20× and 10× objectives, the fields of view were 0.49 and 1.1 mm, with pixel sizes of 0.48 and 1.05 μm, respectively.…”
Section: Multiphoton Microscopementioning
confidence: 99%
“…11 An alternative to time-consuming embedding and physical sectioning of fixed tissue is optical sectioning of unfixed tissue. Imaging unfixed tissue specimens has been demonstrated using techniques such as reflectance confocal microscopy (RCM), [12][13][14][15] confocal fluorescence microscopy (CFM), [16][17][18][19][20][21] multiphoton microscopy (MPM), [22][23][24] structured illumination microscopy, 25 spectrally encoded confocal microscopy, 26 and optical coherence tomography. 27,28 Furthermore, recently it has been demonstrated that fluorescent contrast agents can be rapidly diffused through viable human tissue, enabling fluorescent labeling without fixation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 One potential avenue for reducing reoperation rates following BCS is the use of high-resolution intraoperative imaging to determine if the radial margins are tumor-free during surgery. Optical imaging techniques, including optical coherence tomography, 7 confocal reflectance microscopy, 8 and nonlinear microscopy, 9 are currently being investigated for in-vivo visualization of breast morphology.…”
mentioning
confidence: 99%